Perceraian karena Perselisihan Berkelanjutan dalam Hukum Islam: Perlindungan bagi Pihak yang Dirugikan - Ubaidila; Halimatus Sa'dia (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
Divorce due to ongoing disputes is one of the most frequently cited reasons in divorce cases in Indonesia. From the perspective of Islamic family law, divorce should be the last resort after all reconciliation efforts have failed. This study aims to analyze legal protection for couples experiencing divorce due to prolonged disputes and its implications for women's rights. The research method used is normative juridical with a legislative and Islamic law concept approach. The findings indicate that Indonesian law provides legal protection for those affected by divorce through regulations such as the Marriage Law and the Compilation of Islamic Law. However, in practice, women's post-divorce rights are often overlooked, particularly regarding iddah and mut'ah financial support. Therefore, strengthening the implementation of legal protections and raising legal awareness among the public is necessary to ensure justice in divorce cases, in accordance with the principles of Islamic law.